2018
DOI: 10.1186/s12933-018-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical activity in the development of first cardiovascular disease event: a tree-structured survival analysis of the Danish ADDITION-PRO cohort

Abstract: BackgroundAmbiguity exists in relation to the role of physical activity (PA) for cardiovascular disease (CVD) risk reduction. We examined the interplay between PA dimensions and more conventional CVD risk factors to assess which PA dimensions were associated with the first CVD event and whether subgroup differences exist.MethodsA total of 1449 individuals [median age 65.8 (IQR: 61.2, 70.7) years] with low to high risk of type 2 diabetes and free from CVD from the Danish ADDITION-PRO study were included for sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Hence, the beneficial effect of physical activity in high-risk subgroups is attenuated. However, the registered physical activity level was low in the high-risk subgroups overall making generalisability difficult [41]. Previous interventional studies addressing lifestyle changes have mainly included healthy individuals and excluded participants with pre-existing CAD or CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the beneficial effect of physical activity in high-risk subgroups is attenuated. However, the registered physical activity level was low in the high-risk subgroups overall making generalisability difficult [41]. Previous interventional studies addressing lifestyle changes have mainly included healthy individuals and excluded participants with pre-existing CAD or CVD.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial research supporting a biological role of physical activity to improve cardiovascular health. Past studies have shown that exercise improves endothelial function [39], improves cardiovascular risk factors including glycaemia and lipid levels [40] and reduces incidence of CVD [41]. We did not objectively measure physical activity or physical fitness but relied on self-reported activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a means to general health, physical exercise has a long and storied history and -as intensely suggested by all the major guidelines [111]-remains the cornerstone of lifestyle modification as the first step of non-pharmacological therapeutic strategies for T2DM. Indeed, it is widely known that whilst a sedentary lifestyle is a major risk factor for T2DM and its complications [112], maintaining an appropriate level of physical activity proves to be protective for both incident T2DM and cardiovascular disease [113]. In this setting, in addition to improving both short-term and long-term glycaemic control in T2DM [114], exercise training shows several direct beneficial effects on various organs and systems in T2DM subjects.…”
Section: Effect Of Exercise Trainingmentioning
confidence: 99%